Surfaces in G(1,5) with one apparent double point - Sierra, José Carlos (MATHEMATICA SCANDINAVICA, 2005)
In this work we characterize the smooth surfaces that can be embedded in the Grassmannian of lines G(1,5) with one apparent double point, i.e., such that the general linear projection to G(1,3) produces just one double point. The result is that such a surface must be either a rational scroll of degree 4 or 5 or a Del Pezzo surface of degree 6 or 7.